Polityka pieniężna Europejskiego Banku Centralnego a zagrożenie deflacją w Unii Europejskiej - Bednarczyk, Jan L. (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The aim of the paper is to assess whether the range of non-standard measuresundertaken by the European Central Bank between 2014–2015 may turn outinsufficient to stimulate demand and overcome deflation. The causes for the presentsituation are the weaknesses of mechanisms transmitting monetary policyimpulses to the economy resulting from: 1) pessimistic expectations withinEurozone regarding economic growth, 2) lack among policy tools of any forwardguidance for the desirable mid-term level of crucial real magnitudes, 3) lack ofsufficient flexibility in the inflation target policy, 4) the weakness of the securitiespurchase programmes which exerted only a temporary effect on the ECB’sbalance sheet and monetary base